Empagliflozin Attenuates Obesity-Related Kidney Dysfunction and NLRP3 Inflammasome Activity Through the HO-1–Adiponectin Axis - Ye, Tongtong; Zhang, Jingwen; Wu, Di; Shi, Junfeng; Kuang, Zengguang; Ma, Yuting; Xu, Qian; Chen, Bing; Kan, Chengxia; Sun, Xiaodong; Han, Fang (Frontiers in Endocrinology, 2022)
Empagliflozin (EMPA) is a novel sodium-glucose cotransporter 2 inhibitor (SGLT2i) that produces protective cardiovascular-renal outcomes in patients with diabetes. However, the effects of EMPA on obesity-related kidney disease have not been determined. The heme oxygenase-1 (HO-1)–adiponectin axis is an essential antioxidant system with anti-apoptotic and anti-inflammatory properties. This study explored whether EMPA improves obesity-related kidney disease through regulation of the renal HO-1-mediated adiponectin axis. C57BL/6J mice were assigned to control, high-fat diet (HFD) groups, and EMPA (10 mg/kg) groups. HFD mice showed metabolic abnormality and renal injury, including increased urinary albumin excretion, morphologic changes, and lipid accumulation. EMPA treatment improved metabolic disorders and attenuated lipotoxicity-induced renal injury. Furthermore, EMPA treatment ameliorated renal NLRP3 inflammasome activity and upregulated the HO-1–adiponectin axis. Our findings indicate that EMPA improves obesity-related kidney disease through reduction of NLRP3 inflammasome activity and upregulation of the HO-1–adiponectin axis, suggesting a novel mechanism for SGLT2i-mediated renal protection in obesity.